Camp Funston (Symphony in the Flint Hills, 2013)
After the outbreak of the First World War, the US Army needed training camps to house and train soldiers for the war effort. Fort Riley was selected as the location for the largest of sixteen divisional training camps.
Keywords: World War I; The Great War; Secretary of War; Army; military; Fort Riley; training camp; divisional; cantonment; Frederick Funston; Iola; Kansas; Spanish-American War; detention camp